Enhanced differentiation of human induced pluripotent stem cells toward the midbrain dopaminergic neuron lineage through GLYPICAN‐4 downregulation. (2nd February 2021) - Corti, Serena; Bonjean, Remi; Legier, Thomas; Rattier, Diane; Melon, Christophe; Salin, Pascal; Toso, Erik A.; Kyba, Michael; Kerkerian‐Le Goff, Lydia; Maina, Flavio; Dono, Rosanna
Abstract: Enhancing the differentiation potential of human induced pluripotent stem cells (hiPSC) into disease‐relevant cell types is instrumental for their widespread application in medicine. Here, we show that hiPSCs downregulated for the signaling modulator GLYPICAN‐4 (GPC4) acquire a new biological state characterized by increased hiPSC differentiation capabilities toward ventral midbrain dopaminergic (VMDA) neuron progenitors. This biological trait emerges both in vitro, upon exposing cells to VMDA neuronal differentiation signals, and in vivo, even when transplanting hiPSCs at the extreme conditions of floor‐plate stage in rat brains. Moreover, it is compatible with the overall neuronal maturation process toward acquisition of substantia nigra neuron identity. HiPSCs with downregulated GPC4 also retain self‐renewal and pluripotency in stemness conditions, in vitro, while losing tumorigenesis in vivo as assessed by flank xenografts. In conclusion, our results highlight GPC4 downregulation as a powerful approach to enhance generation of VMDA neurons. Outcomes may contribute to establish hiPSC lines suitable for translational applications. Abstract : Schematic representation of the functional properties acquired by human induced pluripotent stem cells (hiPSCs) following GLYPICAN‐4 (GPC4) downregulation versus control. This includes impaired in vivo tumorigenesis as assessed by flank xenografts, and enhanced differentiation toward ventral midbrain dopaminergic (VMDA) neuron progenitors both in vitro and upon brain transplantation.